PERANCANGAN INTERIOR RUMAH SAKIT IBU DAN ANAK KELAS B KOTA BANDUNG DENGAN PENDEKATAN HEALING ENVIRONMENT - Krisnaldi Krisnaldi; Titihan Sarihati; Erlana Adli Wismoyo (Universitas Mercu Buana, 2021)
In designing a mother and child hospital, the atmosphere of the room needs to be created with reference to the psychological condition and characteristics of the user, which is oriented towards mother and child. The condition of children and women, especially pregnant women, can change drastically which includes psychological and social changes. The hospital environment that feels strange with the presence of new people can trigger anxiety and fear for parents and children. Creating a comfortable environment can help stimulate the patient's healing by reducing anxiety through room organization, circulation, and interior treatment. Treating a comfortable and relaxed atmosphere in the interior of the mother and Child Hospital using the method Healing Environment which focuses on treatment design by combining elements of nature, psychology, and the human senses with hope, creating a comfortable, relaxed atmosphere, reducing anxiety in patients to stimulating patient recovery.